A Retrospective Analysis of Concurrent Pathology in ACL-Reconstructed Knees of Elite Alpine Ski Racers - Jordan, Matthew J. (Orthop J Sports Med, 2017)
BACKGROUND: Anterior cruciate ligament (ACL) tear is the most frequent injury in alpine ski racing, and there is a high prevalence of ACL reinjury. Limited data exist on the concurrent pathology with primary ACL tears in elite alpine ski racers and the magnitude of injury progression after primary ACL reconstruction (ACLR). PURPOSE: To evaluate (1) the involvement of intra-articular and multiligament pathologies at the time of primary ACLR, (2) the subsequent progression in meniscal/chondral injuries, and (3) the occurrence of ACL reinjury in elite alpine ski racers. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Primary ACLR operative reports (n = 28) were obtained for 32 elite alpine ski racers along with the reports of 20 operative procedures that occurred subsequent to primary ACLR. Operative reports were evaluated to identify the presence/location of multiligament injury, meniscal tears, and chondral lesions. RESULTS: At the time of primary ACLR, a majority of knees (82%; 23/28) demonstrated concurrent injury compared with isolated ACL tears; 32% of knees sustained multiligament injuries (9/28), and 8 involved the ipsilateral medial collateral ligament (MCL). Of the ACL-injured knees, 54% had chondral lesions, of which 73% were sustained in the lateral knee compartment, and 82% of meniscal tears (14/17) were complex in nature. Bilateral ACL tears were seen in 22% of the participants, and 28% underwent ACL revision. In the case of ACL revision or future meniscal/chondral surgery, 60% of meniscal tears and 80% of chondral lesions had worsened since the time of primary ACLR. CONCLUSION: Concurrent injury was common in this group of elite ski racers. Primary ACL tears were typically accompanied by lateral compartment chondral lesions and complex meniscal tears that worsened over time. ACL/MCL tears were the most common multiligament injury pattern.